Comportamentos de risco relacionados à saúde entre universitários - Barreto, Lindsei Brabec Mota (2011)
Introduction: Habits and risk behaviors related to health have been responsible for changing the profile of morbidity and mortality in recent decades. Future health professionals, who should tackle and alleviate these problems, are studying in higher education about the importance of adopting a healthy lifestyle, but that is not guarantee that their habits are consistent with the theoretical background they hold. The aim of this study was to verify the presence of risk behaviors to health such as physical inactivity, poor nutrition, overweight / obesity, alcohol consumption and tobacco use among students of 1st and last period of different courses in the health of the Federal University of Sergipe. Methods: A descriptive comparative cross-sectional study with 238 students in the 1st period and 149 students in the last period of the courses of Medicine, Nursing, Dentistry and Physical Education of the Federal University of Sergipe, evaluating food consumption, physical activity level, alcohol consumption and smoke through a validated questionnaire, and level of obesity by calculating body mass index and fat percentage. Results: The students ate at a weekly frequency 1-3 days a week both healthy foods, such as milk, meat, fruits and vegetables, as unhealthy foods, such as soft drinks, sweets, snacks and fried foods. There was a small occurrence of smokers, but 67% of students in the final period began this habit after start their course. There were regular alcohol consumption in all courses, the Physical Education showed the highest occurrence, and 35% of students in the final period began drinking regularly after start their course. There were high rates of inactivity among students of all health courses. Analyzing the body mass index there was occurrence of overweight and obesity, reaching 37% in the last period of Medicine, and comparing students of 1st and last period in almost every course there was an increased of obesity, except Dentistry. The fat percentage data indicate a high occurrence of obesity in men. Conclusion: Although the sample was composed of students in the health area, which in principle have a better knowledge about healthy lifestyle practices, was verified the presence of risk behaviors in their daily habits. Therefore, it is necessary to rethink the relationship between theoretical knowledge and real change in lifestyle of an individual, and do more research to better targeting of strategies for health promotion, based on the regular practice of exercise and changes in food.